Development and application of a real-time polymerase chain reaction method for quantification of Escherichia coli in oysters (Crassostrea gigas). (February 2019) - Miotto, Marília; Fonseca, Antônio A.; Barretta, Clarissa; da Silva, Helen S.; Pellizzaro, Tomás; De Dea Lindner, Juliano; Vieira, Cleide R.W.; Parveen, Salina; Prudencio, Elane S.
Abstract: Oysters are important mariculture species worldwide. Because of their filter-feeding behaviors, oysters can accumulate microorganisms, including pathogens, from surrounding water and concentrate bacteria in high numbers. Rapid and suitable methods for quantification of Escherichia coli in oysters are necessary considering that oysters are perishable foods often consumed raw and some countries use E. coli as the regulatory limit. The objective of this study was to develop a qPCR method for quantification of E. coli in oysters. Additionally, different methods were evaluated for DNA extraction from oyster samples and the more reliable method was chosen. Primers and probe were designed targeting uid A gene of E. coli and shown to specifically amplify DNA from E. coli . Standard curves with bacterial DNA extracted from oysters samples artificially inoculated with E. coli were conducted. A good correlation was noticed when the qPCR method was compared to a culture method in oyster samples. This is the first report of a method exclusively developed for direct quantification of E. coli in oyster, the method showed to be suitable for quantification of E. coli in oysters and could be useful in routine analyses, as it requires less time than the culture method. Highlights: A qPCR method for direct quantification of Escherichia coli in oyster was developed. Three different E. coli DNA extraction methods were evaluated. Comparison of the developed method with a culture method was conducted. The qPCR method allows a good correlation with the culture method in oyster samples.